Faktor-Faktor Yang Berhubungan Dengan Pemberian ASI Eksklusif di Puskesmas Sindang Danau Kabupaten OKU Selatan Provinsi Sumatera Selatan Tahun 2023 - Widiastuti, Rahayu; Afrika, Eka (NHM PRESS, 2024)
Providing proper nutrition in the first six months of a baby's life is by giving milk. Optimal breastfeeding can save the lives of more than 820,000 children under 5 years of age each year. However, only about 36% of babies aged 0-6 months worldwide are exclusively breastfed by the Indonesian Ministry of Health in 2022. The coverage of babies receiving exclusive breastfeeding in 2020 is 66.06% and there has been a decrease in 2021, namely 56.9%. The program target for exclusive breastfeeding in 2020 is 64%. The coverage of exclusive breastfeeding collected in South Sumatra Province in 2020 was 51.6%, decreased compared to 2019 (57.8%). In OKUS district, exclusive breastfeeding is still experiencing ups and downs, in 2016 it was 51.2%, and in 2017 it was 48.5%, in 2018 it was 44.1%, in 2019 it was 43.9%, and in 2020 it was 52, 6%. The purpose of this study was to determine the relationship between knowledge, education, work and family support simultaneously with exclusive breastfeeding at the Sindang Danau Health Center in 2023. Types and Design The study was quantitative using an analytic survey method with a cross sectional approach. The population in this study were all breastfeeding mothers at the Sindang Danau Health Center in 2023. The sample in the study was all breastfeeding mothers, totaling 45 mothers. The results of the univariate analysis obtained from 45 respondents, there were 33 respondents (73.3%) who gave exclusive breastfeeding and 12 respondents (26.7%) who did not. The results of the chi-square statistical test on knowledge variable ρ value = 0.002, education variable ρ value = 0.000 family support ρ value = 0.000 and mother's occupation ρ value = 0.000 less than α = 0.05 indicating that there is a significant relationship between work and breastfeeding exclusively at the Sindang Danau Health Center in 2023.